2018
DOI: 10.2478/pielxxiw-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

An image of nurses and nursing in Poland in the media and in the opinion of various social groups. Systematic review of scientific literature from the years 2010-2017

Abstract: Introduction. Nursing is a profession of public trust with a fairly high position in various rankings examining the prestige of professions. Aim. Analysis of published research results on the image of nurses and nursing in Poland in the media and in the opinion of various social groups. Material and methods. A systematic review of Polish scientific literature from the years 2010-2017 was undertaken. A multi-stage search process was carried out in accordance with the adopted inclusion criteria, and then article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…the insufficient number of professionally active people per number of patients. 68% of respondents stated that [3]. The results of the study showed the same opinion, as up to 80% of respondents declared that the media showed deficiencies in nursing staff.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…the insufficient number of professionally active people per number of patients. 68% of respondents stated that [3]. The results of the study showed the same opinion, as up to 80% of respondents declared that the media showed deficiencies in nursing staff.…”
Section: Discussionsupporting
confidence: 54%
“…Publishers also disseminate information on staff shortages among doctors and nurses [3]. They announce messages about deaths of people waiting for help in the Hospital Emergency Departments or the arrival of paramedics [4].…”
Section: Introduction and Purposementioning
confidence: 99%